Contraception decision-making autonomy among adolescent girls and young women in Uganda - Joseph K.B. Matovu; Dinah Amongin; Martha Akulume; Doreen Tuhebwe; Irene Murungi; Rhoda K. Wanyenze (npj Women's Health)
Abstract We assessed contraception decision-making autonomy among current contraceptive users and interest in self-care-oriented contraception among 2109 sexually-active adolescent girls and young women (AGYW) aged 10–24 years in Uganda. Current contraceptive users were asked about who made the decision to use contraception; those who made the decision on their own were considered to have contraception decision-making autonomy. More than half of AGYW (54.8%, n = 1155) were current contraceptive users; of these, 26.8% (n = 310) made the decision to use contraception on their own. Having contraception discussion with partner prior to contraceptive use (adj. PR = 0.39; 95%CI: 0.32, 0.48) and being currently married (adj. PR = 0.74; 95%CI: 0.56, 0.98) were negatively associated with contraception decision-making autonomy. Fifty-eight percent of AGYW (n = 1213) reported interest in obtaining information on how to access and/or use self-care-oriented contraceptive methods. These findings suggest a need to empower AGYW to not only make but also act on their contraceptive decisions.